Detoxification of hemicellulosic hydrolysates from extracted olive pomace by diananofiltration - Brás, Teresa (2014)
Xylitol can be obtained from the pentose-rich hemicellulosic fraction of agricultural residues, such as extracted olive pomace, by fermentation. Dilute acid hydrolysis of lignocellulosic materials, produces the release of potential inhibitory compounds mainly furan derivatives, aliphatic acids, and phenolic compounds. In order to study the potential on the increase of the hydrolysate fermentability, detoxification experiments based on diananofiltration membrane separation processes were made. Two membranes, NF270 and NF90, were firstly evaluated using hydrolysate model solutions under total recirculation mode, to identify the best membrane for the detoxification. NF270 was chosen to be used in the diananofiltration experiment as it showed the lowest rejection for toxic compounds and highest permeate flux. Diananofiltration experiments, for hydrolysate model solutions and hydrolysate liquor, showed that nanofiltration is able to deplete inhibitory compounds and to obtain solutions with higher xylose content. Conversely to non-detoxified hydrolysates, nanofiltration detoxified hydrolysates enabled yeast growth and xylitol production by the yeast Debaryomyces hansenii, clearly pointing out that detoxification is an absolute requirement for extracted olive pomace dilute acid hydrolysate bioconversion.